Futuring and Envisioning the Future: Definition& Importance - المنصوري, عبدالجليل (Dirasat in Economics and Business, 2008)
No doubt that we are living in a changing world, to a degree that we may say that this is the era of great multiple changes. It is so difficult to adapt to or cope with these changes, unless we put an extra effort to understand them, through equiping ourselves with the skills and tools that enable us to be prepared for the coming future, which is full of the unknowns namely; risks, threats and opportunities. That is simply, the suturing process. Envisioning the future is not a prognostic act, rather it is to put aside the fatalism: it is the art of conjucture. Futuring process is a foresight scanning for the megatrends, and how to anticipate big future surprises. A heuristic process in encountering with the future. The futuring process makes us thinking about the unthinkable, and through the wildcards we make the extrapolation of the trends and their implications that are summed up in the acronym DEGST; (Demography, Economy, Government, Society, and Technology). These trends enable us to see where we are heading to, hence, we can think of it as the top of the hill towards the future, and through the use of scenarios we can take a bird's eye view over the top of the hill, in order to discover new potentials. That is what this paper is all about.